2008
DOI: 10.1007/s00705-008-0158-y
|View full text |Cite
|
Sign up to set email alerts
|

Equine herpesvirus infections in yearlings in South-East Queensland

Abstract: SummaryTwelve nasal swabs were collected from yearling horses with respiratory distress and tested for Equid herpesvirus 1 (EHV-1) and Equid herpesvirus 4 (EHV-4) by realtime PCR targeting the glycoprotein B gene. All samples were negative for EHV-1; however 3 were positive for EHV-4. When these samples were tested for EHV-2 and EHV-5 by PCR all samples were negative for EHV-2 and 11 were positive for EHV-5. All three samples that were positive for EHV-4 were also positive for EHV-5.These three samples gave a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
24
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(31 citation statements)
references
References 39 publications
(38 reference statements)
7
24
0
Order By: Relevance
“…Previous studies from Hungary, Sweden, the UK [21], New Zealand [16], Poland [19], and Iceland [22] have also reported that EHV-2 is more frequently detected than EHV-5. However, in this study, lung tissue and nasal swab samples presented with a higher prevalence of EHV-5 (18.7% and 11.2%, respectively) than that of EHV-2 (13.4% and 5.5%, respectively); this finding corresponds with reports from Australia [10], Ethiopia [20], Korea [13], and Turkey [18]. When measured in different sample types such as peripheral blood mononuclear cells, conjunctival swabs, nasal swabs, or blood, comparable results were discovered in other countries [8,21,23].…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…Previous studies from Hungary, Sweden, the UK [21], New Zealand [16], Poland [19], and Iceland [22] have also reported that EHV-2 is more frequently detected than EHV-5. However, in this study, lung tissue and nasal swab samples presented with a higher prevalence of EHV-5 (18.7% and 11.2%, respectively) than that of EHV-2 (13.4% and 5.5%, respectively); this finding corresponds with reports from Australia [10], Ethiopia [20], Korea [13], and Turkey [18]. When measured in different sample types such as peripheral blood mononuclear cells, conjunctival swabs, nasal swabs, or blood, comparable results were discovered in other countries [8,21,23].…”
Section: Discussionsupporting
confidence: 91%
“…To identify EHV-1, -2, -4, and -5 in each specimen, we used sensitive one-step PCR targeting the conserved sequence of the glycoprotein B gene [20]. PCR amplifications were conducted with a validated pair of primers as described previously, in that individual amplicon size was 190 bp for EHV-1 [26], 444 bp for EHV-2 [10], 677 bp for EHV-4 [26], and 293 bp for EHV-5 [27], for glycoprotein B gene detection and nucleotide sequencing. For each PCR reaction, a sample without DNA was used as a negative control.…”
Section: Dna Extraction and Pcrmentioning
confidence: 99%
See 1 more Smart Citation
“…The different results between younger and older horses could be linked to the different viral phases, with a decreasing amount of virus in older horses, probably latently infected, in comparison to younger mainly acutely infected horses. The young age is more frequently associated with EHV-5 infection and it could represent a confounding factor, in the way that the detection of EHV-5 could be incorrectly considered in association with some pathological condition if an adequate control of healthy animals of the same age is not present in the study (Dynon et al 2007;Diallo et al 2008).…”
Section: Discussionmentioning
confidence: 95%
“…Isolation and genetic characterization of EHV‐2 and EHV‐5 viruses have been carried out worldwide (Browning and Studdert, 1987a; Holloway et al., 1999; Sharp et al., 2007; Wang et al., 2007; Diallo et al., 2008; Fortier et al., 2009; Richter et al., 2009). Previous studies (Murray et al., 1996; Borchers et al., 1997; Dunowska et al., 2002) report that EHV‐2 was an infectious agent in horses showing clinical signs of respiratory infections, but limited information on the role of EHV‐5 in equine respiratory disease exists.…”
Section: Introductionmentioning
confidence: 99%